2016
DOI: 10.1007/s00520-016-3397-6
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensional burden of informal caregivers in primary malignant brain tumor

Abstract: IC burden is multidimensional. Greater provision of formal care, more IC support programs, and economic interventions targeting IC employment and finances are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 47 publications
3
41
0
Order By: Relevance
“…Survivors cited financial stability and the maintenance of benefits, particularly health care, as the primary reasons for maintaining employment throughout treatment. These results are in keeping with prior literature and are unsurprising, because even out‐of‐pocket costs incurred for cancer treatment and lost wages can be quite significant . In addition, similar to recent research, employer accommodations were credited with playing a considerable role in enabling survivors to remain employed throughout treatment initiation.…”
Section: Discussionsupporting
confidence: 86%
“…Survivors cited financial stability and the maintenance of benefits, particularly health care, as the primary reasons for maintaining employment throughout treatment. These results are in keeping with prior literature and are unsurprising, because even out‐of‐pocket costs incurred for cancer treatment and lost wages can be quite significant . In addition, similar to recent research, employer accommodations were credited with playing a considerable role in enabling survivors to remain employed throughout treatment initiation.…”
Section: Discussionsupporting
confidence: 86%
“…The cost of care time was valued by measuring the time spent providing informal care, including time spent on ADL, instrumental activities of daily living (IADL), household activities or time spent with the care recipient at the hospital or medical appointments (Bayen et al, ; Guerriere et al, ; Hanly, Céilleachair, Skally, O'Leary, Kapur, et al, ; Hanly, Céilleachair, Skally, O'Leary, Staines, et al, ; Hanly, Maguire, Balfe, O'Sullivan, & Sharp, ; Palandri et al, ; Van Houtven et al, ; Yabroff & Kim, ; Yu et al, ). Studies using the PGA method to value care time reported the value of informal care as $975 to $19,112 per month with a mean of $4,809 per month ( SD = $6,441; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies using the PGA method to value care time reported the value of informal care as $975 to $19,112 per month with a mean of $4,809 per month ( SD = $6,441; Table ). Bayen et al () used the PGA method, but only valued time spent on ADL, leading to the lowest care time cost of $680 per month. Using the OCA method, the average cost of care time was $2,877 per month ( SD = $1,524) with a range of $1,263–$5,456 per month (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After separation, patients are more likely to be hospitalized and less likely to complete treatment, become involved in clinical trials, or die at home (Glantz et al 2009). Consequences of the disease and caregiving extend beyond this, with caregiver burden having an impact on the financial situation of the family as well (Bayen et al 2016). …”
Section: Consequences Of Family Caregivingmentioning
confidence: 99%